Screening and follow‐up for depression among Arab Americans. Issue 12 (12th August 2018) - Dallo, Florence J.; Prabhakar, Deepak; Ruterbusch, Julie; Schwartz, Kendra; Peterson, Edward L.; Liu, Bin; Ahmedani, Brian K.
Abstract : Background: The authors compared proportions and associations of depression screening, major depression, and follow‐up care of Arab Americans compared to non‐Hispanic whites, non‐Hispanic blacks, Asians, and Hispanics. Methods: Administrative data was electronically abstracted from a large health system in metropolitan Detroit among 97, 918 adult patients in 2014 and 2015. A valid and reliable surname list was used to identify Arab Americans. Using chi‐squares, we examined the relationship between race/ethnicity and depression screening, major depression, and follow‐up care. We calculated odds ratios (OR) and 95% confidence intervals (CI) to examine the relationship between the main independent variable of race/ethnicity and the dependent variables of depression screening and major depression while controlling for confounders. Results: Arab American women were 23% less likely to be screened for depression compared to non‐Hispanic white women (OR = 0.77; 95% CI = 0.70, 0.86). The age‐ and sex‐adjusted proportions of major depression were 5.5% for Arab Americans compared to 7.0% for Hispanics, 6.0% for non‐Hispanic blacks, 5.9% for non‐Hispanic whites, and 1.5% for Asians. Arab Americans with major depression were less likely to follow up with a behavioral specialist and more likely to follow up with a primary care physician compared to other racial and ethnic groups. Conclusions: Our study adds to the discourse on depression care among Arab Americans by highlighting the existing disparities related to adequate screening and appropriate management of depression. Future studies should include information about the influences of acculturation, culture, stigma, family, and religion on depression care.